Sakytinės istorijos galimybės sovietmečio ir posovietinės epochos tyrimuose (atminties kultūros ir istorijos politikos problematikos aspektas) - Švedas, Aurimas (Lietuvos istorijos studijos, 2010)
The Soviet epoch often imposes a professional challenge to a researcher due to the complexities of correct analysis and interpretation of the phenomena and processes of that epoch. All that was left by this epoch, which lasted almost half a century, was fragmentary, uninformative, and contradictory written sources which consciously mislead the researcher by not only preventing an answer to the question "what was it really like?", but also by trying to wrap the researcher in a spider web of reticence, Aesopian language, and open lies. The lack or fragmentation and uninformative nature of the written sources forces historians to use in their research the method of oral history interviews which offers many new perspectives. It could provide much help to the new generation of Sovietologists in Lithuania who adapt the potential method of interview primarily while preparing doctoral theses. A wider use of oral history in Lithuanian historiography (not only by young historians) should be encouraged by the realization that the researchers of the past who use this "methodical tool" acquire a possibility to compose their own "ideal source" or a block of such sources that would be unique in a quantitative and qualitative sense, determining the process of a particular research and fundamentally influencing its insights, providing answers to the questions that are "suppressed" by other historical sources. Good conditions for the development of oral history in Lithuanian historiography are created by a favourable conjuncture in Western historiography—Lithuanian historians have many opportunities to participate in the global academic discourse and contribute to the global research by trying to grasp the issues of the Soviet and post-Soviet epoch. The evaluation of oral history possibilities in the field of research of the Soviet and post-Soviet epoch should include a bigger attention to the debates in the West which focus on the advantages and the disadvantages of this historical method and supplement these debates with insights from the Lithuanian perspective. A closer collaboration of historians and social scientists as well as significant financial investments aimed to support specific research projects and corrections in the evaluation of the production of humanitarian scientists are also very important aspects. The latter aspects of the politics of science have until now impeded the development of oral history in Lithuanian historiography. The possibilities of oral history should be highly estimated while researching the specifics of the culture of memory that emerged in the Soviet epoch and the methods of politics of history which determined that specifics. The information acquired with the help of oral history often plays a crucial role in understanding the efforts of Soviet Party and political elite to create a model of culture of memory that could satisfy its needs as well as in trying to grasp an amount of freedom that a particular historian and all the professional community had in the face of the arsenal of the politics of history. The same applies to the analysis of the situation and activity of the cultural elite which fundamentally influenced the culture of memory and actively participated in the politics of history.